Pengaruh Service Quality Website Hellowork akan Kepuasan Pencari Kerja - Nasrul Ilham Pradana; Lailatul Farida (Universitas Batanghari Jambi, 2023)
This research ambitions to perceive: (1) the simultaneous impact of carrier best which include tangible proof, reliability, responsiveness, warranty, and empathy on activity seeker delight, (2) the partial impact of provider fine inclusive of tangible proof, reliability, power responsiveness, assurance and empathy for activity seeker pleasure. The populace on this research are activity seekers who use the hellowork website provider. The sampling approach in this studies makes use of non-opportunity sampling with a complete sample of 75 respondents. methods of statistics collection using a questionnaire that has been examined for validity and reliability. The records analysis method used to decide the hypothesis of this studies is the classical assumption take a look at, descriptive evaluation, and multiple linear regression evaluation. The effects of this research show that: (1) carrier fine has a simultaneous have an effect on on activity seeker satisfaction, and (2) service first-class has a partially big effect on task seeker satisfaction on real evidence and empathy.